A educação do campo em perspectiva: uma análise do ensino médio, no contexto do campo, no município de Ariquemes, Rondônia - Pulcinelli, Rosenilda Aparecida (2013)
The agricultural model implemented in Brazil there are more than 500 years influenced the agrarian concentration and especially the low investment in education and development of the quality of life rural population. This work has the objective to make a historical analysis of the agrarian question and its influence on the creation of educational public policies specific to the people of the field, assessing its efficacy as to access and permanence of the student in the high schools of the Ariquemes City - Rondônia. Considering also that respect the Federal Constitution 1988, the Law of Guidelines and Bases of Education and the Operational Guidelines for the field education. The methodological procedure used in the research is bibliographical in view of various authors with respect to historical fact of colonization, conquest and the right to quality education for the people of the field, considering also the analysis of models of education and management well as pedagogical proposals giving proper recognition to multiple identities of the populations of the field. So that they can develop an education field with potential community and mostly human. So, were used as a framework document, information of the State Department of Education regarding the implementation and execution of the Project Field School, in the Ariquemes city, the Political Pedagogical Project of School Ricardo Cantanhede, including reports and projects developed in recent years . The results obtained through research though demonstrating a great advance from the 1980s mainly the articulation of civil society - social movements - still does not meet the expectations and needs of rural communities, especially young people. In this sense, it is also necessary to discuss the project to education currently offered the young people of the field, which does not meet their social peculiarities, persisting in the practice of a pedagogy bank and from books. Although not deny the right to the final stages of basic education to the young field in the Ariquemes city - RO also does not contribute to a policy that respects and values their knowledge, highlighting its development, in its fullness, helping your empowerment, self-esteem, and building a more humanized pedagogical practice. For this to occur it is important to consider strengthening a community in the context of socio-educational field, to promote the full exercise of citizenship and education of the individuals field.